Interactive Multimedia Learning Media Assisted by Wordwall to Improve Critical Thinking Skills of Elementary School - Ana, Ria Fajrin Rizqy; Astuti, Leny Suryaning; Wardhani, Indah Setyo (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
This study was motivated by low learning outcomes resulting from a lack of innovation in the use of learning media, with the reliance on lecture and assignment methods often leading to students feeling bored and less interested in learning. The purpose of this study was to develop, test the validity and practicality of, and test the effectiveness of interactive multimedia learning media development assisted by Wordwall in improving the critical thinking skills of elementary school students. This study employs the ADDIE development model. The product testing subjects include subject matter experts, media experts, group testing, and field testing. The data collection instruments used include validation forms, questionnaires, and assessments of critical thinking skills. Furthermore, the analytical method employed in this study is quantitative analysis. The interactive multimedia developed achieved a validity score of 90% from subject matter expert validation and 85% from media expert validation. The multimedia development was also proven to be effective in improving students' critical thinking skills. The N-gain score calculation resulted in a moderate category of 0.59, 81% in the effective category, and a significance value of 0.000 < 0.05, indicating a significant (absolute) difference in effectiveness between the application of interactive multimedia assisted by Wordwall and not using interactive multimedia to improve students' critical thinking skills. The results of this study have implications for improving learning outcomes and increasing the application of digital media in thematic learning at the elementary level more broadly.